IMPROVING READING COMPREHENSION SKILLS IN FOURTH GRADE STUDENTS OF SDN WULUHADEG BY APPLYING "SQ3R" LEARNING MODEL ON "BAHASA INDONESIA" SUBJECT - Nafa Listya Kusumaningrum (Jurnal PGSD Indonesia, 2025)
This study aims to improve the reading comprehension skills of fourth grade students of SDN Wuluhadeg by applying SQ3R learning model on "Bahasa Indonesia" subject. It was a collaborative classroom action research and was done in two cycles. The subjects of this study were the fourth grade students of Wuluhadeg Elementary School. The data collection techniques used were observation, test, and documentation. The data were analyzed qualitatively and quantitatively. The result of this study shows that using SQ3R learning model on the Bahasa Indonesia subject can improve the students' reading comprehension skills. It is proved by the increase on its test results. On the pre-action stage, the percentage of the students' passing grade is 26% with its average score 55.18. Then, at cycle 1, the passing grade is increased up to 65.37% with its average score 70. In addition, at cycle 2, the passing grade is increased up to 100% with its average score 82.40.